Viduslejasvācu valodas fonoloģiskās sistēmas un rakstības ietekme pirmo latviešu rakstu valodā - Vanags, Pēteris (Baltistica, 1997)
INFLUENCE OF THE MIDDLE LOW GERMAN PHONOLOGICAL SYSTEM AND ORTHOGRAPHY ON THE LANGUAGE OF THE EARLY LATVIAN WRITINGS In this article, the author deals with the possible influence of the Low German phonological system and orthography tradition on the language of the Latvian writings in the 16th–early 17lh century. Three types of interference in the vowel system are discussed in the article: under-differentiation of the Latv. /e/ and /æ/ as well as /ē/, /æ/ and /ie/; over-differentiation, as separate phonemes, of the allophones [e] and [ö] of the phoneme /e/ and the allophones [i] and [ü] of the phoneme /i/ in a position next to labial consonants; substitution of Latv. [au] by Low German [ou].